2015
DOI: 10.1111/jvim.12530
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I as Compared to Troponin T for the Detection of Myocardial Damage in Horses

Abstract: BackgroundDifferent cardiac troponin I (cTnI) assays give different results. Only 1 manufacturer has marketed troponin T (cTnT) assays. Therefore, cTnT often is preferred for detection of myocardial infarction in human patients. Studies of cTnT in horses are limited.ObjectivesTo compare a cTnI and a high‐sensitive cTnT assay (hs‐cTnT) in horses.AnimalsCardiac troponin I and cTnT were determined in 35 healthy horses (group 1), 23 horses suspected to have primary myocardial damage (group 2a), and 41 horses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
1
20
0
3
Order By: Relevance
“…Because there are many different cTn assays available, the specific value of the hscTnT assay is described below. The median peak cTnT of 8.0 ng/L in the study population of healthy horses demonstrates that a cTnT cut-off point of 6.6 ng/L, as recently suggested to differentiate between normal horses at rest and those diagnosed with primary myocardial disease, 6 would not be applicable postracing. Cardiac troponin release from the myocardium in response to exercise is not well understood but has clinical implications in the differentiation between cTn concentrations postrace in healthy horses and those with myocardial damage, as discussed below.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Because there are many different cTn assays available, the specific value of the hscTnT assay is described below. The median peak cTnT of 8.0 ng/L in the study population of healthy horses demonstrates that a cTnT cut-off point of 6.6 ng/L, as recently suggested to differentiate between normal horses at rest and those diagnosed with primary myocardial disease, 6 would not be applicable postracing. Cardiac troponin release from the myocardium in response to exercise is not well understood but has clinical implications in the differentiation between cTn concentrations postrace in healthy horses and those with myocardial damage, as discussed below.…”
Section: Discussionmentioning
confidence: 77%
“…Seven research studies in horses have evaluated cTn concentrations in normal horses after nonendurance exercise. None of these studies identified significant increases in cTn concentrations partly as a consequence of the study population sizes (15,28,6,24,26, and 15 horses, respectively) [13][14][15][34][35][36] but also as a result of the use of older generation, 11 conventional sensitivity assays that have a higher LoD. 37,38 We identified significant increases in cTn, using the hscTnT assay, in horses after high-intensity, short-duration racing exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. (2015) [26] demonstrated that despite large quantitative differences, cTnI and cTnT are both useful for detection of myocardial damage in horses but this finding is not in parallel with the findings of Gehlen and et. al.…”
Section: Discussionmentioning
confidence: 90%
“…The next morning, a clinical examination and a more extensive cardiac workup was performed. Serum cardiac troponin I was <0.03 ng/ml (reference range 0.03–0.09 ng/ml) (Van Der Vekens and others 2015). Echocardiography revealed an interventricular septum defect (2.4×3.3 cm on a long axis view), with a shunt velocity of 5.23 m/s, which corresponds to a pressure gradient of 109 mm Hg (P=4v 2 ; where P is the pressure gradient and v is the velocity).…”
Section: Case Presentationmentioning
confidence: 99%